Modified atmosphere packaging with gamma irradiation extending shelf life of strawberry ‘CV’ winter dawn - Saran, F Y; Hassan, M K; Akhther, N (Bangladesh Journal of Nuclear Agriculture, 2025)
An experiment was carried out at the Postharvest Laboratory of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period of February to March, 2023 to find the effects of different postharvest treatments on shelf life and quality of strawberry. The experiment was laid out in completely randomized designs with three replications. There were five treatments, viz. T0: Control (non-irradiated unwrapped), T1: 2.0 KGy gamma irradiated fruits held in 25μ polypropylene bag, T2: 2.0 KGy gamma irradiated fruits held in ambient condition, T3: 2.0 KGy irradiated fruits wrapped in 25μ low-density poly ethylene bag, T4: 2.0 KGy irradiated fruits wrapped in 25μ high-density poly ethylene bag. Data were recorded on weight loss, firmness, color, flavor, shrinkage, freshness, appearance, diseases severity and shelf life at different days after storage. The minimum weight loss (0.73%) was found in 2.0 KGy gamma irradiated fruits wrapped in 25μ polypropylene bag and the maximum weight loss (3.44%) in untreated control strawberry. The longest shelf life (4.0 days) was recorded in 2.0 KGy irradiated fruits held in 25μ polypropylene bag, fruits and the shortest shelf life (3.0 days) was found in untreated control fruits. The findings would greatly contribute to reducing postharvest loss of strawberry and maintaining their quality during storage and marketing at ambient conditions. Bangladesh J. Nuclear Agric, 38(2): 15-25, 2024